Pas de mouvement abolitionniste sans nous ! - Gwenola Ricordeau (Criminocorpus)
This article focuses on abolitionist movements and relatives of prisoners, in particular in France. It draws upon the political experience of the author and abolitionist and feminist analysis. It examines the role of relatives of prisoners (in particular female partners and mothers) in abolitionist struggles, and specific obstacles they face as activists. Finally, the article suggests ways to integrate relatives of prisoners and feminist perspectives in abolitionist struggles.